2017
DOI: 10.4081/gh.2017.575
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal transmission and socio-climatic factors related to paediatric tuberculosis in north-western Ethiopia

Abstract: The burden of tuberculosis (TB) in children reflects continuing and recent transmission within a population. This study aimed to identify spatiotemporal and socio-climatic factors associated with paediatric TB in north-western Ethiopia. Multivariate Poisson regression models were computed using a Bayesian framework. Estimates of parameters were generated using Markov chain Monte Carlo simulation. A total of 2,240 children aged under 15 years diagnosed with TB during the years 2013- 2016 were included in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 54 publications
4
19
1
Order By: Relevance
“…For example, a number of studies used the age prevalence of tuberculin-skin test positivity to measure risks of infection from household and community exposure [ 30 , 31 ]. Previous studies have suggested that areas with high childhood tuberculosis case notification rates may correspond to areas of active transmission [ 32 34 ]; however, only one included covariates to account for potential non-transmission explanations of the spatial distribution of child cases [ 34 ]. Thus, our analysis is the first to provide molecular and epidemiological evidence to corroborate inferences of local tuberculosis transmission with attempts to control for unobserved, spatially heterogeneous, non-transmission factors that may explain the distribution of child cases (such as risk factors for progression of infection, migration of infected individuals into the area, and/or local diagnostic capacity).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of studies used the age prevalence of tuberculin-skin test positivity to measure risks of infection from household and community exposure [ 30 , 31 ]. Previous studies have suggested that areas with high childhood tuberculosis case notification rates may correspond to areas of active transmission [ 32 34 ]; however, only one included covariates to account for potential non-transmission explanations of the spatial distribution of child cases [ 34 ]. Thus, our analysis is the first to provide molecular and epidemiological evidence to corroborate inferences of local tuberculosis transmission with attempts to control for unobserved, spatially heterogeneous, non-transmission factors that may explain the distribution of child cases (such as risk factors for progression of infection, migration of infected individuals into the area, and/or local diagnostic capacity).…”
Section: Discussionmentioning
confidence: 99%
“…Geographic variability exists for multiple health conditions in Ethiopia, particularly infectious diseases [8, 2830]. We previously demonstrated that rates of paediatric TB and multidrug-resistant TB vary across districts in Ethiopia [8, 9]. However, to our knowledge, no previous published study has assessed spatial variability in TB treatment outcomes in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial epidemiological studies have assessed the incidence rates of TB in some parts of Ethiopia [49]. However, to date, no spatial epidemiological analyses of TB treatment outcomes have been reported in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission patterns via genotyping of notified cases and health-seeking behaviors through additional primary data collection as used in similar spatial analysis studies may help our understanding of the results. [91,92]…”
Section: Discussionmentioning
confidence: 99%